The Response of Firms to Maternity Leave and Sickness Absence - Ian M. Schmutte; Meghan M. Skira (Global Labor Organization (GLO), 2020)
The costs to a firm of employee absence depend on how easy it is to find a replacement. We study how firms respond to predictable, but uncertain, worker absences that arise from maternity and non-work-related sickness leave. Using administrative data on over two million spells of leave in Brazil, we identify the short-run effects of a leave spell starting on a firm's employment, hiring, and separations. We find that firms respond immediately to the start of leave by hiring new workers, and to a lesser extent, by limiting job separations. However, firms replace leave-takers at far less than the onefor- one rate implied by a frictionless labor market model. Hiring responses are more pronounced for absences arising in occupations with more transferable skills and in firms operating in thicker labor markets. Altogether, our results suggest that replacing workers using external markets is costly and firms manage predictable worker absences through other channels.
Keywords: J23; J21; J63; J68; J13; 330